THE EFFECTIVENESS THE EFFECTIVENESS OF INFORMATION MEDIA AS A MEANS OF EDUCATING PASSENGERS ABOUT LUGGAGE AT MINANGKABAU INTERNATIONAL AIRPORT - Irawandi, Desviany; Kalbuana, Nawang; Faizal, Irwan (Jurnal Teknologi Kedirgantaraan, 2025)
Information media within the airport environment play a crucial role in educating passengers about baggage regulations, thereby supporting aviation safety and security. However, the effectiveness of such media still requires evaluation, particularly at Minangkabau International Airport. This study aims to analyze the extent to which information media functions as an educational tool for passengers. The research employed a mixed-methods approach, combining quantitative methods through observation and interviews. Quantitative data were analyzed using SPSS software through validity and reliability tests, simple linear regression, and hypothesis testing. The results show that information media have a significant influence on passengers' understanding of baggage regulations, indicated by a β (beta) value of 0.943 and a significance level of p < 0.001. Qualitative findings suggest that the current information media is still suboptimal due to its lack of visual appeal, poor placement, and outdated content. Passengers were more responsive to interactive media such as educational videos and digital infographics. Therefore, a more effective communication strategy is needed by utilizing digital media that is engaging, visual, and easily accessible. This study is expected to serve as a reference in the development of more efficient and educational information media within the airport environment.